Endophytic fungi associated with Hevea spp. and their biocontrol potential against Colletotrichum spp. causing leaf disease - Soumyamol, V.B.; Ruma, S.; Able, P.S.; Roy, C.B. (Rubber Science, 36(2): 2023. 222-229.)
Colletotrichum Leaf Disease (CLD) caused by Colletotrichum acutatum and C. gloeosporioides adversely affect commercial production of natural rubber. Repeated spraying with chemical fungicides to manage the disease pollutes the environment. Bioprospecting of fungal endophytes and their use as biocontrol agents is an effective alternative. Trichoderma spp. is a most promising biocontrol agent that produce antagonistic compounds effective in managing plant diseases. In this study, four sprouting Trichoderma spp. [T. koningii (R12), T. harzianum (L8), T. inhamatum (FX-T) and T. piluliferum (T1)] and a non-sprouting basidiomycete Rigidoporous vinctus (R17) were isolated from leaves and roots of two rubber clones viz. FX 516 and RRII 105 for evaluation of their potential as biocontrol agents against Colletotrichum spp. In the dual culture study, isolate L8 showed 90 and 84 per cent inhibition of radial growth (PIRG) against C. acutatum and C. gloeosporioides respectively followed by T1 which showed 88 PIRG with both C. acutatum and C. gloeosporioides. The isolate R12 showed 89 and 82 PIRG against C. acutatum and C. gloeosporioides respectively. As microbial consortia are more effective than the use of single organism, compatibility tests were conducted for isolate L8 with the other fungal isolates. L8 was compatible with T1, R12 and R17 and incompatible with FX-T. All five fungal isolates were fast growers and were identified based on morphological features.
Keywords: Biocontrol; Colletotrichum leaf disease; Endophytic fungi; Trichoderma